Effect of Nutritional Determinants and TonB on the Natural Transformation of Riemerella anatipestifer - Zhang, Li; Huang, Li; Huang, Mi; Wang, Mengying; Zhu, Dekang; Wang, Mingshu; Jia, Renyong; Chen, Shun; Zhao, Xinxin; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; et al. (Frontiers in Microbiology, 2021)
Riemerella anatipestifer is a gram-negative bacterium that is the first naturally competent bacterium identified in the family Flavobacteriaceae. However, the determinants that influence natural transformation and the underlying mechanism remain unknown. In this study, we evaluated the effects of various nutritional factors of GCB medium (glucose, L-glutamine, vitamin B1, Fe(NO3)3, NaCl, phosphate and peptone), on the natural transformation of R. anatipestifer ATCC 11845. Among the assayed nutrients, iron, phosphate, and peptone affected the natural transformation of R. anatipestifer ATCC 11845 in a mutually independent manner. Given the importance of TonB in nutrient transportation, we further identified whether TonB is involved in the natural transformation of R. anatipestifer ATCC 11845. Mutation of tonBA or tonBB, but not tbfA, was shown to inhibit the natural transformation of R. anatipestifer ATCC 11845 in GCB medium. In parallel, it was shown that the tonBB mutant, but not the tonBA mutant, decreased iron acquisition in GCB medium. This result suggested that the tonBB mutant affects the natural transformation frequency due to the deficiency of iron utilization.